Nutrient recovery in cultured meat systems: Impacts on cost and sustainability metrics - Myers, Gabrielle M.; Jaros, Kate A.; Andersen, Daniel S.; Raman, D. Raj (Frontiers in Nutrition, 2023)
A growing global meat demand requires a decrease in the environmental impacts of meat production. Cultured meat (CM) can potentially address multiple challenges facing animal agriculture, including those related to animal welfare and environmental impacts, but existing cost analyses suggest it is hard for CM to match the relatively low costs of conventionally produced meat. This study analyzes literature reports to contextualize CM’s protein and calorie use efficiencies, comparing CM to animal meat products’ feed conversion ratios, areal productivities, and nitrogen management. Our analyses show that CM has greater protein and energy areal productivities than conventional meat products, and that waste nitrogen from spent media is critical to CM surpassing the nitrogen use efficiency of meat produced in swine and broiler land-applied manure systems. The CM nutrient management costs, arising from wastewater treatment and land application, are estimated to be more expensive than in conventional meat production. Overall, this study demonstrates that nitrogen management will be a key aspect of sustainability in CM production, as it is in conventional meat systems.